Pendampingan Implementasi Kurikulum 2013 untuk Peningkatan Mutu Pembelajaran Guru-guru (POKJA RA) Poncol di Magetan - Mukhibat, Mukhibat; Fitri, Noor Faizatul; Hartati, Afiatun Sri (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2018)
The lack of assistance to the RA Working Group (POKJA RA) Poncol in the implementation of Curriculum 2013, causing the implementation of can not be realized. Base on this, the teachers of RA in sub-district Poncol Magetan urgently require the empowernent in the form at training/assistance continously so that the teacher are able and understand the lgic of preparation of leraning tool according to K-13, the are at least four inportance change of this devotion program, i.e: 1) teacher can fulfil their duties and responsibilities in creating a scientific, creative, and meaningful learning. 2) the emergence of awarness that the development of leraning resourches becames imperative, this is proven by the succesfull communication built with Perpusda Magetan which has never been thought of at all. 3) PTK material has raised awareness and and understanding that improvement in learning should always be done by teacher so that the learning problem that have been faced found the way out. 4) teachers at POKJA RA Poncol have on Permendikbud RI No. 146 year 2014 about K-13 PAUD.